Permanent Income, Liquidity, and Adjustments of Automobile Stocks: Evidence from Panel Data - Lam, P.-S. (Quarterly Journal of Economics, 1991)
A recent article by Bernanke [1984] tests the rational expectations-permanent income hypothesis using panel data on automobile expenditures. He finds no evidence refuting the hypothesis. This paper incorporates a threshold adjustment process into Bernanke's model. Estimations based on a subset of the data used by Bernanke reveal evidence that resale market imperfections and credit market constraints have important effects on automobile expenditures.